Designing a Web-Based Online Opinion Polling System (Case Study: Kampar Regency Transportation Agency) - Marwa, Safni; Adeswastoto, Hanantatur; Finanda, Syawalan (Journal of Engineering Science and Technology Management, 2025)
This study aims to design a web-based online polling system for the Kampar Regency Transportation Agency to improve the effectiveness and efficiency of gathering community aspirations. Public opinion is a crucial foundation for policy-making, particularly in supporting the “Smart Transportation System” initiative. The study was conducted using the Prototyping development model, which includes requirement gathering, quick design, and iterative evaluation. Data collection involved literature reviews, obersrvations, and interviews with agency officials to identify challenges such as geographical barriers and decentralized communication channels. The system was designed using Unified Modelling Language (UML), including Use Case, Activity, and Class Diagrams, to provide a structured blueprint for both the user interface and database. The results demonstrate that the transition from convetional to digital methods provides a centralized, transparent, and accessible platform for the public. The significance of this research lies in its contribution to local government digital transformation, ensuring that community feedback is systematically documented and accurately processed. This system serves as a scalable solution for enchancing public participation and supporting data driven policy evaluation in Kampar Regency.